Ethical Challenges of the European Union Artificial Intelligence Act - Vilfors, Victoria (My University, 2025)
This thesis examined the nature of existing ethical challenges in AI system development and deployment, and how the new European Union Artificial Intelligence Act (Regulation (EU) 2024/1689) addresses these ethical challenges, as well as what ethical challenges and gaps persist despite the newly developed regulations. The motivation of this research was to further the discussion surrounding the new EU AI Act and contribute to expanding the understanding and awareness of what ethical challenges and gaps must be addressed to advance the implementation of EU AI Act in its formative stage. The main research question of this thesis was “What ethical challenges and gaps persist in the European Union Artificial Intelligence Act?”. A qualitative approach was chosen to lay out the ethical landscape of AI system development and deployment in the context of the EU AI Act from the standpoint of fairness, accountability, transparency and ethics (FATE) framework. The primary qualitative research methods used in this thesis were ethical analysis and thematic analysis, as well as the chosen principles of fairness, accountability and transparency. The research approach for this thesis was chosen due to the novelty of the newly imposed legislation and rapidly developing nature of subject of artificial intelligence. Notable gaps and challenges identified in this thesis include challenges that stem from the difficulty of defining fairness, where AI system providers could use gerrymandering to manipulate the interpretation of fairness and indicate that the system under development is fair. Another ethical challenge and gap related to accountability in governance and enforcement of the regulations is that companies might not be equipped to foster a certain level of self-governance, creating a concern about how well the regulations will be enforced and the AI systems audited. The fast-approaching deadline for compliance has also been identified as problematic for AI system deployers, due to uncertainty of how to comply with the new regulations. Additionally, a gap related to algorithmic transparency was identified, and the so-called black box problem persists. Despite the efforts of the AI Act, the level of transparency and explainability that is required for the regulations to be effective might be unrealistic, because of complex supply chains and the overall complexity of AI models. Moreover, the effects of generative AI on individual’s lives and society have not been given enough consideration, because despite problematic cases with generative AI, generative AI remains outside of the high-risk classification and therefore is subject only to transparency requirements. The EU AI Act is however, currently in its formative stage, because of the novelty of the regulations, and the legal and ethical practices concerning the new regulations are still forming. There are no real-world cases that can be used as example case studies where the EU AI Act was implemented. This thesis also highlights the tentative state of the enforcement of the EU AI Act, because the legal and ethical practices concerning the new regulations are still forming and there are no real-world cases that can be used as concrete examples of the AI Act in motion. In other words, the interpretations of the EU AI Act are constantly evolving as regulators, institutions legal bodies and other stakeholders engage with the regulation. The conclusions and interpretations drawn from this thesis should be considered open to revision due to the evolving nature of interpretations and enforcement of the AI Act in real-world situations.

Tässä tutkielmassa tarkasteltiin tekoälyjärjestelmien kehittämisen ja käyttöönoton eettisten haasteiden luonnetta sekä sitä, miten uusi Euroopan Unionin tekoälyasetus (asetus (EU) 2024/1689) vastaa näihin eettisiin haasteisiin, ja mitä eettisiä haasteita ja puutteita on edelleen olemassa uusista säännöksistä huolimatta. Tutkimuksen tarkoituksena oli edistää keskustelua uudesta EU:n tekoälyasetuksesta ja lisätä ymmärrystä ja tietoisuutta siitä, mihin eettisiin haasteisiin ja puutteisiin on puututtava EU:n tekoälyasetuksen täytäntöönpanon edistämiseksi sen muodostumisvaiheessa. Tutkielman päätutkimuskysymys oli "Mitä eettisiä haasteita ja puutteita Euroopan unionin tekoälyasetuksessa on edelleen?". Laadullinen lähestymistapa valittiin tekoälyjärjestelmien kehittämisen ja käyttöönoton eettisen maiseman hahmottamiseksi EU:n tekoälyasetuksen kontekstissa oikeudenmukaisuuden, vastuuvelvollisuuden, läpinäkyvyyden ja etiikan (FATE) viitekehyksen näkökulmasta. Tässä tutkielmassa käytetyt ensisijaiset laadulliset tutkimusmenetelmät olivat eettinen analyysi ja temaattinen analyysi sekä valitut oikeudenmukaisuuden, vastuuvelvollisuuden ja läpinäkyvyyden periaatteet. Tutkimuslähestymistapa valittiin uuden lainsäädännön uutuuden ja tekoälyn aihealueen nopeasti kehittyvän luonteen vuoksi. Tässä opinnäytetyössä tunnistettuja merkittäviä puutteita ja haasteita ovat muun muassa oikeudenmukaisuuden määrittelemisen vaikeudet, joissa tekoälyjärjestelmien tarjoajat voisivat käyttää gerrymandering-menetelmää manipuloidakseen oikeudenmukaisuuden tulkintaa ja osoittaakseen, että kehitteillä oleva järjestelmä on oikeudenmukainen. Toinen eettinen haaste ja aukko, joka liittyy hallinnon ja säännösten täytäntöönpanon vastuullisuuteen, on se, että yrityksillä ei välttämättä ole valmiuksia edistää tietyn tason itsehallintoa, mikä herättää huolta siitä, kuinka hyvin säännöksiä valvotaan ja tekoälyjärjestelmiä auditoidaan. Nopeasti lähestyvä määräaika säännösten noudattamiselle on myös tunnistettu ongelmalliseksi tekoälyjärjestelmien käyttöönottajille, koska on epävarmaa, miten uusia säännöksiä noudatetaan. Lisäksi havaittiin algoritmien läpinäkyvyyteen liittyvä aukko, ja niin sanottu musta laatikko -ongelma on edelleen olemassa. Tekoälylain ponnisteluista huolimatta säännösten tehokkuuden edellyttämä läpinäkyvyyden ja selitettävyyden taso saattaa olla epärealistinen monimutkaisten toimitusketjujen ja tekoälymallien yleisen monimutkaisuuden vuoksi. Lisäksi generatiivisen tekoälyn vaikutuksia yksilöiden elämään ja yhteiskuntaan ei ole pohdittu tarpeeksi, koska generatiivisen tekoälyn ongelmallisista tapauksista huolimatta se jää korkean riskin luokituksen ulkopuolelle ja siksi siihen sovelletaan vain läpinäkyvyysvaatimuksia EU:n tekoälyasetus on kuitenkin vielä muotoutumassa säännösten uutuuden vuoksi, ja uusiin säännöksiin liittyvät oikeudelliset ja eettiset käytännöt ovat vielä kehittymässä. Ei ole olemassa käytännön tapauksia, joita voitaisiin käyttää esimerkkitapauksina EU:n tekoälyasetuksen täytäntöönpanosta. Tämä tutkielma korostaa myös EU:n tekoälyasetuksen täytäntöönpanon kehittyvää tilaa, koska uusiin säännöksiin liittyvät oikeudelliset ja eettiset käytännöt ovat vielä muotoutumassa, eikä ole olemassa käytännön tapauksia, joita voitaisiin käyttää konkreettisina esimerkkeinä tekoälyasetuksen soveltamisesta. Toisin sanoen EU:n tekoälyasetuksen tulkinnat kehittyvät jatkuvasti sääntelyviranomaisten, instituutioiden, oikeusviranomaisten ja muiden sidosryhmien osallistuessa sääntelyyn. Tästä tutkielmassa tehtyjä johtopäätöksiä ja tulkintoja tulisi pitää avoimina muutoksille tekoälyasetuksen tulkintojen ja täytäntöönpanon kehittyvän luonteen vuoksi.
Keywords: artificial intelligence, generative artificial intelligence, ethics of ai, eu ai act, ai act, tekoäly, generatiivinen tekoäly, tekoälyn etiikka, eu:n tekoälyasetus, tekoälyasetus